CIVIL AVIATION AS A TARGET OF INTERNATIONAL TERRORISM - Zülfükar Aytaç KİŞMAN (Fırat University, 2020)
Terrorism is a phenomenon that often emerges by adapting to the character of the era. Terrorist acts, which can vary according to variables such as the character of the period, the place, the target audience, etc. can cause various negative effects in almost every area of life. Terrorism activities constitute a great danger for the civil aviation sector, too, which is one of the most important developments in our age and serving nationally and internationally. In fact, the terrorist incidents have prevented the development of the Civil Aviation sector from time to time and created periods of stagnation, causing it to be not preferred and thus affecting the civil aviation sector in economic, commercial, social and psychological terms. Terror attacks that took place in the Civil Aviation sector affected many people regardless of race and country because of the nature of the sector and reached at remarkable dimensions. Considering the characteristics of terrorism such as disrupting social peace by inflicting fear and terror, blocking the flow of daily life, causing damage to people's trust in legal authority, it is seen that terrorist acts in the civil aviation sector serve these purposes. When the international dimension of the civil aviation sector is taken into account, the reflection of these negative effects caused by terrorist acts is more noticeable. In this study, the development and history of civil aviation with its national and international dimensions have been examined. Starting from the emergence of terrorism activities, the events that have affected the civil aviation sector have been stated by giving examples, and the results and solutions regarding the issue have been put forward.